Pengaruh Current Ratio, Return on Equity dan Market to Book Ratio Terhadap Harga Saham - Nada Wulantika; Dedi Hariyanto; Heni Safitri (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the effect of Current Ratio (CR), Return On Equity (ROE) and Market to Book Ratio (MBR) on the stock price of Property Sector, Real Estate and Building Construction Services Companies as of 30 December 2016. The sampling technique used in this study is purposive sampling method. Based on predetermined sample selection criteria, there were 58 companies. The analysis technique used is normality test, multicollinearity, autocorrelation, heteroscedasticity, linearity, multiple linear regression, multiple correlation coefficient (r), determination coefficient (R2), simultaneous hypothesis testing using F test and partially by using t test. The results of the normality test show that all data is normally distributed with asym, sig. (2-tailed) Unstandardized Residual of 0,823 greater than 0,05. For simultaneous test results using the F test shows that the three independent variables are CR, ROE, MBR together have a significant effect on the dependent variable (Stock Price) as evidenced by the calculated F value of 5,317 and sig. amounting to 0,003 which is smaller than 0,05. While the partial test results using the t test shows that the independent variables namely CR and ROE have no significant effect on the dependent variable (Share Price) while the independent variable is the MBR has a significant effect on the dependent variable (Stock Price) as evidenced by the value of t count CR of -0,118 and has a sig value. amounting to 0,907 which is greater than 0,05, the ROE t count value is 1,467 and has a sig value. amounting to 0,147 greater than 0,05 and the calculated value of the MBR is 2,639 and has a sig value. amounting to 0,011 which is smaller than 0,05.